Domestic courts, transnational law, and international order. (September 2020) - Kahraman, Filiz; Kalyanpur, Nikhil; Newman, Abraham L.
This article revisits the relationship between law and international order. Building on legal research concerned with transnational law, we argue that domestic courts are endogenous sites of international political change. National courts are constitutive of international order by generating new rules, adjudicating transnational disputes, and bounding state sovereignty. We illustrate the ways in which national courts create new political opportunities by updating three core international relations theory debates. Recognizing the role of domestic courts as global adjudicators enhances our understanding of regime complexity and international forum shopping. By re-interpreting aspects of conventional international law, and engaging in cross-border dialogue, domestic courts challenge our understanding of international diffusion and judicialization. By redefining the boundaries of state authority and sovereignty, national courts create potential for conflict and cooperation. A transnational law perspective illustrates the porous nature between domestic and international spheres, highlighting how domestic courts have become adjudicators for state and non-state actors that operate across mainstream levels of analysis. Our approach calls on scholars to move beyond analyzing national legal systems as mechanisms of compliance to instead consider domestic courts as co-creators of international order.